80.5k views
5 votes
75 - 3.5y - 4y = 4y + 6
Solve for y please.

2 Answers

3 votes

Answer:

6

Explanation:

75−3.5y−4y=4y+6

Step 1: Simplify both sides of the equation.

75−3.5y−4y=4y+6

75+−3.5y+−4y=4y+6

(−3.5y+−4y)+(75)=4y+6(Combine Like Terms)

−7.5y+75=4y+6

−7.5y+75=4y+6

Step 2: Subtract 4y from both sides.

−7.5y+75−4y=4y+6−4y

−11.5y+75=6

Step 3: Subtract 75 from both sides.

−11.5y+75−75=6−75

−11.5y=−69

Step 4: Divide both sides by -11.5.

−11.5y

−11.5

=

−69

−11.5

y=6

Hope this helps!

User Gurjeet
by
5.9k points
5 votes

Answer: 6

Explanation:

75 - 3.5y - 4y = 4y + 6

We solve by collecting like terms i.e.

75 - 6 = 4y + 4y + 3.5y

69 = 11.5y

y = 69/11.5

y = 6

User WholesomeGhost
by
5.9k points